To Prove & verify that :
x³ + y³ = (x + y)(x² - xy + y²)
x³ - y³ = (x - y)(x² + xy + y²).
Proof for 1st Identity :
★ x³ + y³ = x (x² - xy + y²) + y(x² - xy + y²)
⟶ x³ + y³ = x³ - x²y + xy² + x²y - xy² + y³
⟶ x³ + y³ = x³ + y³
Proof for 2nd identity :
★ x³ - y³ = x(x² + xy + y²) - y(x² + xy + y²)
⟶ x³ - y³ = x³ + x²y + xy² - x²y - xy² - y³
⟶ x³ - y³ = x³ - y³
For example,
Let us assume that,
x = 1
y = 2
So,
✯ x³ + y³ = 1³ + 2³
⟹ (x + y)(x² - xy + y²) = 1 + 8
⟹ (1 + 2)(1² - (1)(2) + 2²) = 9
⟹ 3 * (1 - 2 + 4) = 9
⟹ 3 * 3 = 9
⟹ 9 = 9
✯ x³ - y³ = 1³ - 2³
⟹ (1 - 2) * (1² + (1)(2) + 2²) = 1 - 8
⟹ ( - 1) * (1 + 2 + 4) = - 7
⟹ ( - 1) * (7) = - 7
⟹ - 7 = - 7
Thus , they can be called as identities/formulae as they are very useful in finding the value of a certain equation or an expression easily.
I hope it will help you.
Regards.